Sistem Pendukung Keputusan Pemilihan Penyidik Pegawai Negeri Sipil (PPNS) dengan Menggunakan Metode Electre Studi Kasus: Balai Wilayah Sungai Sumatera II Medan - Delvi Sitinjak (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
The Civil Servant Investigator is one of the law enforcement officers that has the function to carry out an investigation process that is given special authority to carry out an investigation process for a violation of the Regional Government Legal Product (PERDA) which contains elements of criminal acts. Usually the crime is not a general crime that can be handled by police investigators. In making the decision on the selection of Civil Servant Investigators (PPNS) at the Medan Sumatera River Region II Medan the writer uses the Electre method, where Electre is one of the methods for determining the order or priority in MCDM (Multi-Criterion Decision Making). In the use of decision support systems with the Electre method will provide a matching rating value for each alternative. In it all data are combined into one with the weight of the assessment that has been obtained through test assessment. The author tries to design and build a decision support system for the selection of Civil Servant Investigators using the Electre method, providing information needed by the committee in making decisions and applying the Electre Method in determining the Civil Servant Investigator Balai Sumatera River Region II Medan Medan Decision support system is not a making tool decision, but rather a system that helps decision makers by equipping them with information from data that has been processed with relevance and is needed to make decisions about an issue more quickly and accurately